Reading scripture with the reformers - George, Timothy (Downers Grove, IL : IVP Academic, 2011)
Timothy George takes readers through the exciting events of the sixteenth century, showing how this dynamic period was instigated by a fresh return to the Scriptures. He immerses us in the world of the Reformation, its continuities with the ancient and medieval church, and its dramatic upheavals and controversies. Most of all, he uncovers the significant way that the Bible shaped the minds and hearts of the reformers.
Why read the reformers? -- Ad fontes! -- The Erasmian moment -- Whose Bible? which tradition? -- Doctor Martinus -- Lutheran ways -- Along the Rhine -- Preach the Word.
Includes bibliographical references and indexes.
Keywords: Bible -- Criticism, interpretation, etc. -- History -- 16th century; Reformation; Church history -- 16th century